The Role of Reconsolidation and the Dynamic Process of Long-Term Memory Formation and Storage - Alberini, Cristina M. (Frontiers in Behavioral Neuroscience, 2011)
It is becoming increasingly clear that the processes of memory formation and storage are exquisitely dynamic. Elucidating the nature and temporal evolution of the biological changes that accompany encoding, storage and retrieval is key to understand memory formation. For explicit or medial temporal lobe-dependent memories that form after a discrete event and are stored for a long time, the physical changes underlying the encoding and processing of the information (memory trace or engram) remain in a fragile state for some time. However, over time, the new memory becomes increasingly resistant to disruption until it is consolidated. Retrieval or reactivation of an apparently consolidated memory can render the memory labile again, and reconsolidation is the process that occurs to mediate its restabilization. Reconsolidation also evolves with the age of the memory: Young memories are sensitive to postreactivation disruption, but older memories are more resistant. Why does a memory become labile again if it is retrieved or reactivated? Here I suggest that the main function of reconsolidation is to contribute to the lingering consolidation process and mediate memory strengthening. I also discuss the literature and results regarding the influence of the passage of time on the reconsolidation of memory. These points have important implications for the use of reconsolidation in therapeutic settings.